The Revival of Virtue Ethics As an Ethical View - Chris O. Abakare (Universitas Negeri Makassar, 2021)
Aristotle and Plato were the chief architects of virtue ethics, but their own formulation of virtue ethics was mostly subdued with the appearance of consequentialism as well as Kantian deontology. However, modem thinkers have attempted to revive virtue ethics in its new form and in this regard the name which is popularly known is G.E.M. Anscombe. In fact Anscombe clearly indicates in what sense virtue ethics can be revived and what was wrong with the traditional virtue ethics as expounded by Aristotle and Plato. Anscombe points out three important issues for which traditional virtue ethics perhaps lost its glory. First, moral philosophy in general cannot survive without an adequate philosophy of psychology and this thing was absent in the traditional virtue ethics. Secondly, without psychological possibility the concepts of moral obligation and moral duty, the moral sense of ought to be jeopardized. Thirdly and importantly, the differences between the well-known English writers on moral philosophy from Sidgwick to the present day are of little importance. This task of this paper is to review the revival of virtue ethics.